2020
DOI: 10.1186/s12864-020-06904-4
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of sex allocation in the parasitoid wasp Nasonia vitripennis

Abstract: Background: Whilst adaptive facultative sex allocation has been widely studied at the phenotypic level across a broad range of organisms, we still know remarkably little about its genetic architecture. Here, we explore the genome-wide basis of sex ratio variation in the parasitoid wasp Nasonia vitripennis, perhaps the best studied organism in terms of sex allocation, and well known for its response to local mate competition. Results: We performed a genome-wide association study (GWAS) for single foundress sex … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 114 publications
(134 reference statements)
1
5
0
Order By: Relevance
“…Note that this approach is different from generating artificial isofemale lines, which are used to produce genetically homogenous individuals to study the genetics of certain traits (e.g. [ 136 ]). Strains from nest boxes and from carrion were kept in different rooms at constant light.…”
Section: Methodsmentioning
confidence: 99%
“…Note that this approach is different from generating artificial isofemale lines, which are used to produce genetically homogenous individuals to study the genetics of certain traits (e.g. [ 136 ]). Strains from nest boxes and from carrion were kept in different rooms at constant light.…”
Section: Methodsmentioning
confidence: 99%
“…Aside from forward genetic approaches described above, Nasonia is amenable to reverse genetic approaches, such as RNA interference ( Lynch and Desplan 2006 ; Werren et al 2009 ). The utility of the Nasonia genus model system to identify the genetic basis of a wide variety of biological traits of evolutionary importance has been amply demonstrated in recent years ( Gadau et al 2002 ; Verhulst et al 2010 ; Loehlin and Werren 2012 ; Brucker and Bordenstein 2013 ; Niehuis et al 2013 ; Hoedjes et al 2014 ; Martinson et al 2017 ; Funkhouser-Jones et al 2018 ; Pannebakker et al 2020 ; Zou et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The strains used in Malec et al (2021) had been cultured in the laboratory for over 20 generations. However, maternal Wolbachia transmission is not 100% (Hoffmann et al, 1990;Turelli et al, 1992) and prolonged laboratory rearing has been reported to result in loss of the Wolbachia infection in N. vitripennis strains (Pannebakker et al, 2020). This is crucial, as Wolbachia-infected males are incompatible with Wolbachiauninfected females, leading to different degrees of offspring reduction (Breeuwer and Werren, 1990;Bordenstein and Werren, 1998;Bordenstein et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Giesbers et al, 2013;Bell and Bordenstein, 2022) and evolutionary genetics (e.g. van de Zande et al, 2014;Pannebakker et al, 2020). Its most well-known and cosmopolitan species, Nasonia vitripennis, has been proposed to be differentiated into two ecotypes distinguishable by their respective microhabitats (Schröder, 2000;Malec et al, 2021; Figure 1).…”
Section: Introductionmentioning
confidence: 99%